Autophagy up and down by outsmarting the incredible ULK. Issue 5 (4th May 2017) - Nazio, Francesca; Cecconi, Francesco
ABSTRACT: Macroautophagy/autophagy initiation is finely regulated by post-translational modifications of key proteins, to comply with the fast kinetics of the cellular response to several stress stimuli. Phosphorylation and ubiquitination play a central role in controlling autophagy by influencing the activity, recruitment and turnover of autophagic components. Recently, we found that, upon autophagy progression, ULK1 kinase is specifically ubiquitinated by the E3 ligase NEDD4L and then degraded via the proteasome. However, during prolonged autophagy, while the ULK1 protein undergoes this inhibition, ULK1 mRNA is actively transcribed, translated and then inhibited again by MTOR-dependent inhibitory phosphorylation. This regulation is essential to promptly restore the ULK1 protein to its original levels to keep autophagy under a safe and physiological threshold.